Effects of combined interventions to optimize recovery during high-intensity exercises in trained individuals - Fernando G. Beltrami; Linus Hanselmann; Christina M. Spengler (Bern Open Publishing, 2023)
Background Team sports such as ice hockey offer the opportunity of recovery breaks between high-intensity work intervals. Strategies aiming to mitigate fatigue during intermittent physical activity are seldom investigated in combination, although several different mechanisms of action exist, which might be cumulative and therefore beneficial for athletes. This study examined the effects of seven combined recovery interventions (enhanced recovery package, ERP) on exercise capacity during intermittent high-intensity cycling. Methods Sixteen trained men (age: 24.8 ± 3.4 y; maximal power output: 5.0 ± 0.5 W･kg-1) completed a repeated sprint exercise (RSE) protocol consisting of six 30-s cycling sprints with 3-min breaks between each sprint. The first sprint was always performed at a similar load, while sprints 2-6 were performed with the ergometer in cadence dependent mode (0.075 kg･kg-1). During the breaks, the ERP, Placebo, or Control protocols were applied, all on different days. The ERP condition combined 1) 3-min ice gel packs to the neck; 2, 3) 5-s mouth rinsing of a 10% carbohydrate and caffeine (6 mg･kg-1), 4) ingestion of 50 ml of a 6% carbohydrate solution, 5, 6) 30 s of all-out hyperventilation while breathing 100% O2 (hyperoxia); and finally, 7) potentiation maneuvers via performance of 3 half-squats at 75% of one maximal repetition. The placebo intervention masked the interventions except for the ice packs and potentiation maneuvers. Participants were told they were performing a simplified version with only the known beneficial interventions. Power output, heart rate, blood lactate concentration, rate of perceived exertion and gas exchange were compared between the ERP and Placebo conditions. Results Mean power output (W) was significantly higher for the ERP condition compared to Placebo (570 ± 74 W vs. 560 ± 71 W, t(15) = 4.603, P < 0.001, 95% CI diff = 5 - 14 W, dz = 1.15). The rate of power decrement over sprints 2-6 was very similar between trials (ERP -14.2 W per sprint, 95% CI = -21.6 - -6.8 W; Placebo -17.4 W per sprint, 95% CI = -24.7 - -10.2 W per sprint, P = 0.407). Mean heart rate was higher (3 ± 4 bpm, P = 0.012) for the ERP compared to the Placebo condition, as was breathing frequency (2.4 ± 4.0 breaths･min-1, P = 0.028) and respiratory exchange ratio (0.12 ± 0.06, P < 0.001). Oxygen uptake was 80 ± 109 ml･min-1 (P = 0.013) lower for ERP. No differences were found with regards to the rate of perceived exertion or blood lactate concentration. Conclusion ERP optimized recovery when applied during the breaks of a high-intensity repeated sprint exercise and shows a small but consistent increase in mean power output. It is possible that the ERP prevented a loss of aerobic efficiency. A top-down approach when tailoring packages for individual athletes might overcome the issue of small improvements that are difficult to detect when strategies are tested in isolation.